EVALUASI STRATEGI PERIKLANAN DAN PEMASARAN INTERAKTIF PADA FORWARD EVENT CREATOR - Andy Gondowijoyo (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2017)
Along with the development of creative industries in 2015-2016, especially in the field of bazaar, causing higher competition in Surabaya. Pop-up Market or commonly called “Bazaar” is one of the creative industries in Surabaya growing in 2015 - 2016. With the advent of Pop-up Market sizeable and successful as Basha Market On Market Go !, WTF Market, Kepo Market, Conquro Market, Hype Market, HIVE Market, Market of the day, Rascal Market and many bazaar in Surabaya, make many agencies to take business opportunities by creating a new bazaar. This requires creative industries to choose and implement advertising strategies and proper marketing, interactive marketing in particular, given the development of the virtual world in order to increase sales and visitors in an event. The purpose of this study was to obtain the results of the evaluation of interactive marketing and advertisings strategies of the company Forward Event Creator. This study is a qualitative research with an informant as much as 8 people consisting of 3 participants in the event, one person owner of the company, two employees of the company, a interactive marketing expert and an advertising expert through interviews with eight informants. The results in this study indicate that the need to choose the advertising medium by considering several aspects and increase online advertising media. Interactive marketing media should also be added, not only to use Instagram only.